CHEMICAL HAZARDS IN PHARMACEUTICAL INDUSTRY: AN OVERVIEW - Agarwal, Princy; Goyal, Anju; Vaishnav, Rajat (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The pharmaceutical industry is a vital component of health-care systems all over the world engaged in discovery, development, manufacture, and marketing of medicines for human as well as animal health. Pharmaceutical industries also have many environmental problems, like the other chemical industries. The pharmaceutical industry is based primarily on the scientific formulation, research, and development of drugs, that is, helpful in the prevention or treatment of diseases and disorders. The manufacturing of APIs and formulation processes involves the use of various chemicals which includes various corrosive and irritant agents such as acids, bases, oxidizing and reducing agents, solvents, and many more which can be found sometimes at very high concentrations and are hazardous to health of persons performing the various processes during manufacturing and formulation of API and medicines. The effective management of the chemical risks linked to the handling of these agents is mandatory for the safety of the workers in the industry, ethically and also legally as per the rules and guidelines of various acts regulating the functioning of the pharma industry. This article provides a comprehensive review of various chemical hazards generally encountered by the pharmaceutical industry, its management and regulation in India.